Molecular, cellular and circuit basis of cholinergic modulation of pain - Naser, Paul; Kuner, Rohini (Neuroscience, 2018)
Here, we aim to review the considerable progress in our understanding of peripheral, spinal and brain contributions to cholinergic modulation of pain. We discuss the distribution of cholinergic neurons, muscarinic and nicotinic receptors over the central nervous system and the synaptic and circuit-level modulation by cholinergic signaling. AchRs profoundly regulate nociceptive transmission at the level of the spinal cord via pre- as well as postsynaptic mechanisms. Moreover, we attempt to provide an overview of how some of the salient regions in the pain network spanning the brain, such as the primary somatosensory cortex, insular cortex, anterior cingulate cortex, the medial prefrontal cortex and descending modulatory systems are influenced by cholinergic modulation. Finally, we critically discuss the clinical relevance of cholinergic signaling to pain therapy.
Available online 8 September 2017
Gesehen am 24.09.2018